SWOT Analysis Using Matrix and Calculation of IFE and EFE at UMKM Warcaf Titik Singgah - Febrianto, Dika; Daspar, Daspar (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This study aims to look at the business strategy of Warcaf Titik Singgah MSMEs through the SWOT method and the IFE and EFE matrix. The results show that Warcaf is in Quadrant III, which means there is a great opportunity to improve its internal weaknesses. In addition to fixing operations and human resource issues, the suggested strategy is to optimize opportunities such as campus collaboration, menu innovation, and digital marketing. Warcaf Titik Singgah is expected to increase its competitiveness in the competitive coffee shop industry with this method. This research emphasizes how important it is to apply strategic management if we want community-based MSMEs to survive and thrive.